Study Of Compensatıon For Anterıor Open-Bıte In Hıgh-Angle Skeletal Class 2 Cases - Hakan N. İşcan; Ali S. Gültan (Galenos Yayinevi, 1988)
In the present study to investigate the regions of compensation mechanisms in dento-maxillo-facial system involved for the prevention of anterior open-bite in high-angle skeletal class 2 growing cases, 17 subjects with skeletal and dental open-bite were compared with 17 subjects showing skeletal open-bite but a mean overbite of 2.12 ± 0.50 mm. In cephalometric comparison of two groups in regard with maxillo-facial morphology and dentoalveolar structural characteristics; among the cranial, maxillary, mandibular, maxillo-mandibuhr, facial height and dental parameters, gonial angle, cant of ramus, effective length of the mandible, lower anterior facial height, and anterior facial height, posterior facial height, overbite, upper and lower posterior vertical dentoalveolar height, upper anterior vertical dentoalveolar height and inclination of the upper incisors showed statistically significant differences between the groups.